Femtosecond Laser Induced Nanowire Technique and Its Applications. (29th May 2011) - Baba, Motoyoshi; Jia, Tianqing; Suzuki, Masayuki; Kuroda, Hiroto
Abstract : Semiconductor nanowires are very attractive due to their interesting fundamental properties and enormous potentials for device applications to the nanoscale optoelectronics and solar cells, and so forth. We fabricated semiconductor nanowires of various wire parameters such as wire length, diameter, and density by femtosecond laser induced method. We report the development of our technology of creating semiconductor nanowires with smaller size than the laser wavelength at precise position by femtosecond laser ablation technique. There are a variety of growth methods for nanowires including chemical vapor deposition (CVD), molecular-beam epitaxy (MBE), and pulsed laser deposition (PLD). Although PLD has recently been applied as a growth method for nanowires, laser induced nanowires are very good in quality. Their growth rate is much higher than that of nanowires grown by other ways. We discuss the growth mechanism of laser induced nanowires and describe the advantages of this approach.